Exploring the role of CASPR2 in neuropathic pain - Tseng, M (2023)
Neuropathic pain is caused by a lesion or disease affecting the somatosensory nervous system affecting 7-10% of the general population. Neuropathic pain is characterised by pathophysiological changes within the nervous system that trigger disordered transmission of sensory signals. There is a critical need for targeted therapeutics for neuropathic pain, as current treatments are challenged by limited efficacy and poor tolerance. Understanding the induction and mechanism of neuropathic pain is crucial for the development of novel, efficacious therapies for its treatment.